DINAMIKA IMPLEMENTASI KONSEP SISTEM TANGGUNG RENTENG DAN KONTRIBUSINYA PADA TERCAPAINYA ZERO BAD DEBT - Syaiful Arifin (Jurnal Keuangan dan Perbankan, 2008)
Co-operation realizing togetherness and member prosperity, more and more becamea solution in replying global challenge and regional newly. Pursuant to analysis result ofresearch which had been conducted to co-operation of woman saving and loan in region ofTown Probolinggo in the reality co-operation managed by all this womankind was dynamicenough. It was proven because 31,25% among others were always as the commitment ofsystem norm account the renteng. The comitment was looked from its management dynamicswhich always respected the togetherness, the core importance in specifying decision.The caseof stipulating of membership status and also case of comitment togetherness to account theloss when it happened did not bill the members. Something else from the result finding ofthis research was that in reality the dynamism of system management account the renteng hadthe linearity to make-up of net income (SHU), even in the reality it also affected positively toalloted net income. A fact empirically proved that system account the renteng represented thesocial capital which could not be disregarded. Managing economy was an entity like cooperation.